Pengaruh Customization dan Interdependensi terhadap Karakteristik Informasi Sistem Akuntansi Manajemen Broad scope dan Aggregation - Ietje Nazaruddin; Subhan Fajry (Journal of Accounting and Investment, 2005)
This study examined empirically whether the relation between customization and characteristic of management accounting systems, especially broad scope and aggregation information is a direct one or whether the relation operates via interdependence. The purpose of this study is to reexamine the result of Bouwens (1998) and Bouwens and Abernethy (2000) and Anggraini (2003) study which revealed there was not strong support for characteristic of broad scope management accounting systems and aggregation of information for uncertainty in managerial decision makings. This is different from earlier studies of Mia Chenhall (!994), Abernethy Gutherie (1994), Chong (1998). This theory suggests that customization has a direct effect on the use characteristic of management accounting systems, but also that customization augments interdependence between departments which in turn affect characteristic of management accounting systems use. Responses of 87 managers (production and marketing) were analyzed by  Path analysis is used to test the model. The result of this study confirms the studies of Bouwens (1998) and Bouwens and Abernethy (2000) but differs the study of Anggraini (2003). Customization does not influence characteristic management accounting systems  broad scope and aggregation information use via interdependence.